The trouble with tippers - Baxter, Nicola; Ball, Geoff (London : Anness Publishing, Ltd., 2016)
This is a super-sized first reading book for 3-5 year olds, with an engaging story, colourful pictures and point-and-say words to learn. A super-size floor book format means that everybody can read along and see the pictures. It includes amusing stories, repeated vocabulary and brightly coloured pictures on every page that help children to feel confident as they build up their reading skills. Other titles in this series include The Trouble with Trains, The Trouble with Tractors and The Trouble with Trucks . It helps you to follow the troublesome tipper as it hurries through the day, causing mayhem as it crashes into a car, falls into a hole and has to be dug out by a digger. The fun colourful pictures and silly story in this book help to make reading at home successful and enjoyable. This book can be used in several ways to help beginning readers gain confidence. Start by reading the illustrated words at the edge of each left-hand page with your child, then have fun trying to spot the same words and pictures in the story itself. Finally, the illustrated words can be found at the end of this book so that you can check all the words that have been learnt
Primary
Keywords: Building -- Juvenile fiction; Bulldozers -- Juvenile fiction; Construction equipment -- Juvenile fiction; Machinery -- Juvenile fiction; Big books; Children's stories -- Pictorial works; Readers -- Elementary